2005
DOI: 10.2754/avb200574040557
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pomiferin Premedication on the Antioxidant Status of Rats with Ischemia-Reperfused Kidney

Abstract: The aim of this study was to analyze the relationship between the antioxidant effect and the dose of pomiferin during a prophylactic administration. The pathological model for an in vivo experiment was the unilateral ischemia-reperfusion of the laboratory rat kidney. The animals were randomly divided into five groups. Pomiferin was administered orally at doses of 5, 10 and 20 mg·kg -1 , in 2 ml of Avicel solution by a gastric sound once a day to three premedicated groups. A placebo -2 ml of 0.5% Avicel solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Lycopene has been known to be an effective antioxidant [30] as well as an anti-proliferative compound against several cancers [31]. Isopomiferin which is a derivative of plant-based compound pomiferin has been known to exhibit anti-microbial properties, anti-inflammatory agent, effective agent against diabetes and a potent antioxidant (Table 1) [32,33]. Density functional theory is a computer-based approach with procuring immense popularity in the field of in silico analysis.…”
Section: Fig 1 Flowchart Of Methodologymentioning
confidence: 99%
“…Lycopene has been known to be an effective antioxidant [30] as well as an anti-proliferative compound against several cancers [31]. Isopomiferin which is a derivative of plant-based compound pomiferin has been known to exhibit anti-microbial properties, anti-inflammatory agent, effective agent against diabetes and a potent antioxidant (Table 1) [32,33]. Density functional theory is a computer-based approach with procuring immense popularity in the field of in silico analysis.…”
Section: Fig 1 Flowchart Of Methodologymentioning
confidence: 99%
“…An anti-inflammatory potential was also ascribed to pomiferin [27,32]. also in vivo animal models [25,26]. On the other hand, it showed also a mild pro-oxidant effect in cell-based models [27].…”
Section: Introductionmentioning
confidence: 92%
“…Mouse hepatic microsomes were used to determine the EROD activity (7-ethoxyresorufin-O-deethylase) of osajin and pomiferin 19 . In vivo studies confirmed the scavenging potential of osajin and pomiferin too [20][21] . Among various reactive oxygen species (ROS) generated during pathological processes, which cause or accompany ischemia/reperfusion (I/R) injury, O -2• plays the key role.…”
Section: Introductionmentioning
confidence: 57%